Beyond automation with CFEngine 3 - Burgess, Mark S. (O'Reilly Media, 2014)
"Learn how to go beyond classical automation with CFEngine 3, one of the most established configuration management systems available. In this video tutorial, host and CFEngine creator Mark Burgess takes you on a tour of discovery from basic automation concepts to more complex examples, such as implementing distributed orchestration."--Resource description page.